Supplier selection : an MCDA-based approach - Mukherjee, Krishnendu (Studies in systems, decision and control ;, 2017)
The purpose of this book is to present a comprehensive review of the latest research and development trends at the international level for modeling and optimization of the supplier selection process for different industrial sectors. It is targeted to serve two audiences: the MBA and PhD student interested in procurement, and the practitioner who wishes to gain a deeper understanding of procurement analysis with multi-criteria based decision tools to avoid upstream risks to get better supply chain visibility. The book is expected to serve as a ready reference for supplier selection criteria and various multi-criteria based supplier's evaluation methods for forward, reverse and mass customized supply chain. This book encompasses several criteria, methods for supplier selection in a systematic way based on extensive literature review from 1998 to 2012. It provides several case studies and some useful links which can serve as a starting point for interested researchers. In the appendix several computer code written in MatLab and VB.NET is also included for the interested reader. Lucid explosion of various techniques used to select and evaluate suppliers is one of the unique characteristic of this book. Moreover, this book gives in depth analysis of selection and evaluation of suppliers for traditional supply chain, closed loop supply chain, supply chain for customized product, green supply chain, sustainable supply chain and also depicts methods for supply base reduction and selection of large number of suppliers.